Análise do comportamento reológico de pastas de cimento contendo resíduos de pneu para poços de petróleo - Melo, Abimael Lopes de (2009)
The low tenacity presented by the Portland cement pastes used in the oil wells cementation has been motivating several researches with attention focused on alternative materials. Additives have been developed to generate flexible pastes with mechanical resistance capable to support the expansions and retractions of the metallic covering of the wells that submit to the steam injection, technique very used to increase the recovery factor in oil reservoirs with high viscosity. A fresh paste with inadequate rheological behavior may commit the cementation process seriously, involving flaws that affect the performance of the paste substantially in the hardened state. This work proposes the elaboration and the rheological analysis of Portland cement pastes with addition of residues of rubber tire in several proportions, with the aim of minimizing the damages provoked in the hem cementing of these wells. By thermogravimetric analysis, the particles of eraser that go by the sieve of 0,5mm (35 mesh) opening and treated superficially with NaOH solution of 1 mol/L presented appropriate thermal resistance for wells that submit to thermal cyclic. The evaluation of the study based on the results of the rheological analysis of the pastes, complemented by the mechanical analysis, thickening, stability, tenor of free water and filtrate loss, being used as parameter a paste reference, without rubber addition. The results showed satisfactory rheology, passive of few corrections; considerable loss of mechanical resistance (traction and compression), compensated by earnings of tenacity, however with established limits for its application in oil wells; satisfactory stability, free water and thickening time